PEMANFAATAN DAUN PINUS JARUM UNTUK DIJADIKAN BRIKET BIOCOAL SEBAGAI ENERGI LISTRIK ALTERNATIF - Fitriani Said; Herawati Herawati (Jurusan Teknik Elektro, Fakultas Teknik, Universitas Borneo Tarakan, 2021)
Biomass is organic material produced through the photosynthetic process in the form of products or waste. Examples of biomass include plants, trees, grass, agricultural waste, forest waste, feces and livestock manure. This biomass can be used as an alternative fuel to replace petroleum which is suitable for development in Tarakan. One of the abundant sources of biomass is needle pine leaves which are found on the UBT campus, Pesisir Charity Beach and Tarakan City Nursery. The selection of fallen needle pine leaves as biomass in this study was based on the absence of utilization of pine leaf waste. Thus, in this study, dry needle pine leaf waste will be utilized to make briquettes mixed with coal with a variant of adhesive composition. There are 3 types of adhesives used, sago, starch starch and clay. Of the 3 types of adhesives, each sample was tested to obtain the value of moisture content, ash content, heat and electrical energy. Briquettes can be said to be good if they have a water content value below 8% according to SNI. Where the water content in the sago adhesive is in the range of more than 6%, while for starch adhesive it is in the range of 5%-6% and for clay adhesive the value is in the range of 5%-7%. The ash content in this study has met the SNI standard, which is below 8%, but the clay adhesive has an ash content close to 8%, which is 7.95%. The value of voltage and current is influenced by the composition of the sample, where the smaller the percentage of the pine leaf content, the smaller it is, and vice versa. The calorific value is obtained from the analysis of existing data to obtain a large enough heating value, which is in the range of 4500 J.